Assessment of pre-hospital and in-hospital factors leading to delays in initiation of treatment in patient with ST segment elevation myocardial infarction - Kashyap, Jeet Ram; Sood, Ishita; Kashyap, Rashmi (International Journal Of Community Medicine And Public Health, 2020)
Background: India has the highest burden of acute coronary syndrome (ACS) patients in the world. While managing patients with ACS, especially those with acute ST elevation myocardial infarction (STEMI), time plays an important role in determining the morbidity and mortality. Methods: An observational prospective study was conducted among patients admitted with symptomatic STEMI. Questionnaire based information was obtained regarding demographic profile, risk factors, treatment seeking behaviour including duration and reasons for delay and treatment in the hospital. Outcome was assessed at discharge and at 30 days. Results: A total of 100 patients were given a definite diagnosis of STEMI. The mean age was 55.38 (SD 10.28) years. Majority 80 (80%) were males and females constituted 20%. Sedentary lifestyle was the major risk factor present in sixty (60%) patients. The median time from symptoms to hospital was 420 min (range 30-2880 minutes). Only 17% patients reached hospital within 2 hours of symptoms and 37% between 2 to 6 hours and 46% after 6 hours. Thirty five patients (35%) thought it to be a heart attack. Hospital delay was recorded in 50% patients with ECG done in more than 10 minutes. Outcome at 30 day depicted as mortality in three patients with loss to follow in 18 (18%) and angina in 6 out of 81 (7.4%) patients. Conclusions: Both pre hospital and in hospital delays have adverse effect on the outcome and thus efforts should be made to minimize these delays.